2021
DOI: 10.1007/s00592-021-01752-4
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine and diabetes: back to the future?

Abstract: The first reports of a link between thiamine and diabetes date back to the 1940s. Some years later, a role for thiamine deficiency in diabetic neuropathy became evident, and some pilot studies evaluated the putative effects of thiamine supplementation. However, the administration of thiamine and its lipophilic derivative benfotiamine for the treatment of this complication gained consensus only at the end of the ‘90 s. The first evidence of the beneficial effects of thiamine on microvascular cells involved in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…Vitamin B 1 is a cofactor of enzymes involved in PPP; therefore, its use increases among patients with DM [ 30 , 31 , 32 ]. Vitamin B 1 deficiency among DM patients may contribute to the development of diabetic nephropathy [ 16 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B 1 is a cofactor of enzymes involved in PPP; therefore, its use increases among patients with DM [ 30 , 31 , 32 ]. Vitamin B 1 deficiency among DM patients may contribute to the development of diabetic nephropathy [ 16 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B 6 deficiencies are most often correlated with deficiencies of other B vitamins and often affect the elderly and those on HD as well as people with homocysteinemia [ 9 ]. In our previous study, we observed that 40% of HD patients had low dietary vitamin B 6 intake [ 34 ]. Bevier et al found that vitamin B 6 concentrations decreased by 25.4% after one dialysis session [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thiamine transport protein system is primarily responsible for thiamine absorption in the duodenum. Thiamine is transported and delivered into tissues by two transporters, thiamine transporter 1 (THTR1) and thiamine transporter 2 (THTR2) [ 4 ]. The placenta, liver, and kidney are among the tissues that contain high levels of THTR1 and THTR2, but THTR1 is also present in skeletal tissues and cardiac muscles [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Несколько лет спустя роль дефицита тиамина в развитии ДПН стала очевидной, а в некоторых пилотных исследованиях оценивали предполагаемые эффекты добавок тиамина. Однако применение тиамина и его липофильного производного бенфотиамина для лечения данного осложнения получило официальное одобрение только в конце 90-х годов прошлого века [23].…”
unclassified